1970
DOI: 10.1113/jphysiol.1970.sp009069
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion from cerebral ventricle to cisterna magna in the unanaesthetized cat. Effect of calcium on body temperature

Abstract: SUMMARY1. A method is described for the perfusion of the liquor space from a lateral cerebral ventricle to the cisterna magna in the unanaesthetized cat.Perfusions were carried out for 30-40 min using various physiological salt solutions whilst rectal temperature was recorded.2. When the salt solution used contained calcium in the physiological concentration, rectal temperature remained unchanged, but when it contained no calcium an intense hyperthermia developed during the perfusion. The finding that calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(32 citation statements)
references
References 7 publications
6
26
0
Order By: Relevance
“…Recently, it has been found that a change in the ratio of sodium to calcium ions in the cerebral ventricles or in the posterior HYPOTHALAMIC IONS AND TEMPERATURE hypothalamus produces consistent changes in body temperature, in the same direction, in several species including the cat (Feldberg, Myers & Veale, 1970;, the rabbit (Feldberg & Saxena, 1970), the monkey (Myers, Veale & Yaksh, 1971) and in the rat (Myers & Brophy, 1971). In each of these species, the fact that the temperature is 37.00 C or thereabouts at birth, would support the view that a mechanism, such as the postulated ionic one for the set-point, is present at parturition although the capacity to thermoregulate against heat or cold may not be adequate .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that a change in the ratio of sodium to calcium ions in the cerebral ventricles or in the posterior HYPOTHALAMIC IONS AND TEMPERATURE hypothalamus produces consistent changes in body temperature, in the same direction, in several species including the cat (Feldberg, Myers & Veale, 1970;, the rabbit (Feldberg & Saxena, 1970), the monkey (Myers, Veale & Yaksh, 1971) and in the rat (Myers & Brophy, 1971). In each of these species, the fact that the temperature is 37.00 C or thereabouts at birth, would support the view that a mechanism, such as the postulated ionic one for the set-point, is present at parturition although the capacity to thermoregulate against heat or cold may not be adequate .…”
Section: Discussionmentioning
confidence: 99%
“…A change in the ratio of sodium to calcium ions in the artificial cerebrospinal fluid (CSF) perfused through the cerebral ventricles produces consistent changes in body temperature in the same direction in the cat (Feldberg, Myers & Veale, 1970;, rabbit (Feldberg & Saxena, 1970a, b), monkey (Myers, Veale & Yaksh, 1971), rat (Myers & Brophy, 1971) and sheep (Myers, 1974). Feldberg et al (1970) suggested that in homoeothermic animals the constancy of temperature depends on the balance of sodium and calcium ions in the anterior hypothalamus and that calcium ions may act as a kind of 'brake' and prevent the sodium ions from exerting their hyperthermic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Although the onset of the hyperthermic responses was usually between 1 and 10 min after the injection, the duration of the fever produced was often difficult to assess, especially with larger doses, because of the interference encountered from a non-specific fever of slow onset. This latter fever, which has been described by other workers (Feldberg, Myers & Veale, 1970;Feldberg & Saxena, 1970) and is thought to be due to an unknown pyrogenic factor, normally developed between 1 and 3 h after an injection. At such time the shorter duration hyperthermias produced by lower doses of RX72601 were completed, whilst the rises in temperatures produced by large doses of RX72601 were still in evidence.…”
Section: Intraventricular Injections Of Rx72601mentioning
confidence: 91%